2000
DOI: 10.1111/j.1528-1157.2000.tb04602.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Calcium Channels by Group I and Group II Metabotropic Glutamate Receptors in Dentate Gyrus Neurons from Patients with Temporal Lobe Epilepsy

Abstract: Summary:Purpose: Metabotropic glutamate receptors (mGluRs) might be promising new drug targets for the treatment of epilepsy because the expression of certain mGluRs is regulated in epilepsy and because activation of mGluRs results in distinctive anti-and proconvulsant effects. Therefore, we examined how rnGluR activation modulates high-voltageactivated (HVA) Ca2' channels.Methods: Whole-cell patch-clamp recordings were obtained from granule cells and interneuron-like cells acutely isolated from the dentate gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In the developing cochlea, P/Q-type and N-type Ca 2+ channels support efferent release of neurotransmitter, whereas L-type Ca 2+ channels suppress release by activating Ca 2+ -dependent large conductance potassium (BK) channels that repolarize the efferent terminals (Zorrilla de San Martin et al 2010). Previous work in central neurons has shown that agonists of mGluRs can reduce currents through L-type Ca 2+ channels (Sayer et al 1992;Sahara & Westbrook, 1993;Pin & Duvoisin, 1995;Schumacher et al 2000). Thus, group I mGluR activation in the developing cochlea might enhance efferent inhibition by suppressing L-type Ca 2+ channels, preventing activation of BK channels, and prolonging terminal depolarization and neurotransmitter release.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the developing cochlea, P/Q-type and N-type Ca 2+ channels support efferent release of neurotransmitter, whereas L-type Ca 2+ channels suppress release by activating Ca 2+ -dependent large conductance potassium (BK) channels that repolarize the efferent terminals (Zorrilla de San Martin et al 2010). Previous work in central neurons has shown that agonists of mGluRs can reduce currents through L-type Ca 2+ channels (Sayer et al 1992;Sahara & Westbrook, 1993;Pin & Duvoisin, 1995;Schumacher et al 2000). Thus, group I mGluR activation in the developing cochlea might enhance efferent inhibition by suppressing L-type Ca 2+ channels, preventing activation of BK channels, and prolonging terminal depolarization and neurotransmitter release.…”
Section: Discussionmentioning
confidence: 96%
“…; Sahara & Westbrook, ; Pin & Duvoisin, ; Schumacher et al . ). Thus, group I mGluR activation in the developing cochlea might enhance efferent inhibition by suppressing L‐type Ca 2+ channels, preventing activation of BK channels, and prolonging terminal depolarization and neurotransmitter release.…”
Section: Discussionmentioning
confidence: 97%
“…The involvement of action potentials in the elevation of extracellular glutamate by DHPG could indicate that the effect is not mediated by presynaptic terminals. However, the capacity of mGluR1 and mGluR5 to increase cytosolic Ca 2ϩ via stimulating release from the endoplasmic reticulum or opening L-type Ca 2ϩ channels indicates a presynaptic priming effect on vesicular release that would not necessarily be revealed by blocking action potential-induced activation of N-type Ca 2ϩ channels (Kammermeier et al, 2000;Schumacher et al, 2000). Demonstrating a priming action by mGluR1 and mGluR5, Cochilla and Alford (1998) found that although mGluR1 stimulation did not produce excitatory potentials, it potentiated the magnitude of electrically stimulated EPSPs in motor neurons.…”
Section: Characterization Of the Pharmacological Action Of Dhpg Infusmentioning
confidence: 99%
“…Group II mGluRs have been previously shown to be G icoupled, negative modulators of L-and N-type Ca 2ϩ channels in electrophysiological studies using brain slices, neuronal cultures, and heterologous expression systems (Chivas et al, 1994;Schumacher et al, 2000). Similarly, in vitro and in vivo release studies reveal L-and N-type channel involvement in the inhibition of dopamine release by group II mGluRs (Hu et al, 1999).…”
Section: Group II Metabotropic Glutamate Receptors Inhibit Glutamate mentioning
confidence: 99%